Da missa à militância: a trajetória religiosa-política do padre Antônio Melo Costa no município do Cabo de Santo Agostinho-Pernambuco (1963-1977). - Gomes, Ricardo Jorge Silveira (2022)
This paper is based on the problematization and contextualization of Father Antônio Melo Costa’s religious and political trajectory — who has influenced thousands of people in their struggle to overcome economic and social issues —, while working in the Catholic Church in the city of Cabo de Santo Agostinho-PE in the 1960s and 1970s. The research has resorted to Max Weber (1991) theoretical basis about the concept of charismatic leadership and its multiple faces, and to the concept of the social doctrines of the Catholic Church, according to Bozzo (2005). Also, Cândido (2012) was the basis for the texts and documents pertaining to the political participation of Padre Melo, considering the agrarian question in Brazil in face of its history. Given to this context, the aim of this paper is the investigation of the priest, assuming that he was on behalf of great landowners, despite his conviction based on the ideals of the Social Doctrine of the Church. Qualitative approach with interdisciplinary focus has been used on analysis and discussion of the results, including exploratory research with the use hypothetico-deductive method. Regarding the research procedures, bibliographical research, documentary research, and data processing have been employed. With all his history of successes and failures, the image of Father Melo’s leadership is that of a “remarkable personality” through the eyes of friends and enemies, allies and political opponents, religious and non-religious opponents, fellow countrymen and foreigners, sympathizers and non-sympathizers. Father Melo was a man, and every man has weaknesses and strengths, truths and lies, hopes and disappointments, kindness and evil, love and hate, doubts and certainties.